The Gardening Bug and Gardens for Bugs: Urban Pollinator Gardening, Social Contagion, and Conservation - Murphy, Atticus. (Tufts University. Tisch Library., 2025)
Thesis (Ph.D.)--Tufts University, 2025.; Submitted to the Dept. of Biology.; Advisor: Elizabeth Crone.; Committee: Colin Orians, Michael Reed, and Caleb Scoville.; Keyword: Ecology.